EDH: Endothelium-dependent hyperpolarization and microvascular signaling. - Garland, C; Dora, K (Wiley, 2016)
Endothelium-dependent hyperpolarizing factor (EDHF) is a powerful vasodilator influence in small resistance arteries and thus an important modulator of blood pressure and flow. As the name suggests, EDHF was thought to describe a diffusible factor stimulating smooth muscle hyperpolarization (and thus vasodilatation). However, this idea has evolved with the recognition that a factor(s) can operate the spread of hyperpolarizing current from the endothelium to the vascular smooth muscle (VSM). As such, the pathway is now termed endothelium-dependent hyperpolarization (EDH). EDH is activated by an increase in endothelial [Ca(2+) ]i , which stimulates two Ca(2+) -sensitive K-channels, SKC a and IKC a . This was discovered because apamin and charybdotoxin applied in combination blocked EDHF responses, but iberiotoxin a blocker of BKC a was not able to substitute for charybdotoxin. SKC a and IKC a channels are arranged in endothelial microdomains, particularly within projections toward the adjacent smooth muscle, which are rich in IKC a channels, and close to inter-endothelial gap junctions where SKC a is prevalent. KC a activation hyperpolarizes endothelial cells, and K(+) efflux through them can act as a diffusible 'EDHF' by stimulating VSM Na(+) /K(+) -ATPase and inwardly-rectifying K-channels (KIR ). In parallel, hyperpolarizing current spreads from the endothelium to the smooth muscle through myoendothelial gap junctions located on endothelial projections. The resulting radial EDH is complemented by spread of 'conducted' hyperpolarization along the endothelium of arteries and arterioles to affect conducted vasodilatation (CVD). Retrograde CVD effectively integrates blood flow within the microcirculation, but how the underlying hyperpolarization is sustained is unclear. This article is protected by copyright. All rights reserved.